The political culture of Judaism - Sicker, Martin (Westport, Conn. : Praeger, 2001)
Sicker examines the fundamental issues of the relationship of the individual to society and state, the implications for public policy of the Judaic focus on social justice, and the rabbinic approach to the problems of national security, from the perspective of a distinctive Judaic political culture that emerges from the source documents and traditions of classical Judaism.
The foundations of Judaic civilization -- Democratic theocracy -- The idea of consent -- Nomocracy, or the regime of halakhah -- The individual and society -- Social justice -- National security.
Includes bibliographical references (pages 145-153) and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Judaism and politics; Jewish ethics; Ethics, Jewish; RELIGION -- Judaism -- Theology; Jewish ethics; Judaism and politics; Jodendom; Politieke cultuur; Electronic books